La Universidad Central durante la Segunda República: las facultades de ciencias y su contexto internacional - RIBAGORDA, ALVARO; Lopez-Ocon, Leoncio (Historia de las Universidades, 2022)
During the Second Spanish Republic, a series of reforms were promoted in the university system to encourage its renewal. An attempt was made to democratise the institution and promote its autonomy. The aim was to bring Spanish universities into line with the most important Western universities by means of various educational innovations and the integration of research activity within the faculties. As a result of these efforts, Spanish science took off after Cajal was awarded the Nobel Prize for Medicine in 1906 and the JAE was created the following year. This work studies the transformations that took place in this reformist context in the faculties of Medicine, Science and Pharmacy at the University of Madrid. It analyses their origins, their curricula and their protagonists, considering the achievements and limitations of the reforms carried out on this scientific campus. Particular attention is paid to the composition of the professors of these faculties, their selection system through competitive examinations, the growing integration of women in university classrooms, many of them linked to the Residencia de Señoritas, and the presence of university students in the media, particularly radio. Aspects of the complex and convulsive international context are also taken into consideration. Thus, the situation of the universities of Portugal, Austria and Argentina in those years is presented, given their parallels, contrasts and interrelationships with the Universidad Central and the scant knowledge of them in the Spanish historiographical panorama.